1982
DOI: 10.1037/0022-006x.50.4.546
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive models of criminal violence based upon intelligence and psychopathy levels.

Abstract: An earlier study identified a high risk for violent crime in psychopathic prisoners when intelligence was considered as a moderator. The present investigation of 168 male prisoners sought to identify more specific models of violence relating to psychopathic status by considering additional cognitive factors that might relate to intelligence and to the expression of physical aggression. Three cognitive psychopathic models were suggested by the data. An impaired-processing psychopathic model of violent crime, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0
3

Year Published

1983
1983
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 49 publications
(44 reference statements)
2
32
0
3
Order By: Relevance
“…IQ has been proposed to moderate the effect of psychopathy on violence such that low IQ psychopaths present greater risk for violence than do high IQ psychopaths and high and low IQ nonpsychopaths (Heilbrun 1979(Heilbrun , 1982(Heilbrun , 1990. Conversely, there is also evidence that IQ and psychopathy combine to predict violence in an additive, rather than a multiplicative manner (Holland, Beckett, and Levi, 1981).…”
Section: Iqmentioning
confidence: 99%
“…IQ has been proposed to moderate the effect of psychopathy on violence such that low IQ psychopaths present greater risk for violence than do high IQ psychopaths and high and low IQ nonpsychopaths (Heilbrun 1979(Heilbrun , 1982(Heilbrun , 1990. Conversely, there is also evidence that IQ and psychopathy combine to predict violence in an additive, rather than a multiplicative manner (Holland, Beckett, and Levi, 1981).…”
Section: Iqmentioning
confidence: 99%
“…Gorenstein (1982) did not control for level of intelligence in his study, although he indicated that education was relatively homogeneous between comparison groups. It is possible, then, as Heilbrun (1982) suggested, that intelligence is an important moderator variable which influences behavior among psychopaths.…”
Section: Introductionmentioning
confidence: 99%
“…These features have been associated with a violent environment and sociocultural deprivation (Silva, Derecho, Leong, Weinstock, & Ferrari, 2001). Empathy deficits are related to inadequate identification of emotional expressions (Marsh et al, 2008;Petroni et al, 2011), reward-oriented behaviour without concern for the consequences (Brazil et al, 2011) and deficits in executive functions such as inhibitory control and working memory (Heilbrun, 1982;Nelson & Trainor, 2007;Paschall & Fishbein, 2002). Furthermore, theory of mind, an empathy-related process (Ibanez et al, 2013), has effects on behavioural, emotional and moral judgement control in violent individuals (Ragsdale, Foley, & Lauwereyns, 2011).…”
mentioning
confidence: 99%
“…In addition, impairments in executive functions are another important factor in individuals with deficiencies in social interactions (Brazil et al, 2011;Heilbrun, 1982;Nelson & Trainor, 2007;Paschall & Fishbein, 2002). Moreover, in populations with antisocial personality disorder and psychopathic behaviour, impairments in executive function have often been observed (Brazil et al, 2011;Salnaitis, Baker, Holland, & Welsh, 2011).…”
mentioning
confidence: 99%